Postinfarction right ventricular wall dissection with left-to-right shunting. (4th October 2018) - Okamura, Homare; Arakawa, Mamoru; Takeuchi, Taro; Adachi, Hideo
Abstract: Ventricular septal rupture is an uncommon fatal complication of acute myocardial infarction. In rare cases, the rupture can extend into the right ventricular free wall and cause intramyocardial dissection. We describe the case of a patient who developed postinfarction right ventricular free wall dissection with left-to-right shunting and successfully underwent patch repair.